KOMUNIKASI POLITIK PADA TRADISI PEMBERIAN GALA SANGSAKO DALAM KEBUDAYAAN MINANGKABAU - Irvan Habibi Saputra; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Political communication has actually existed in the environment of the community since it was thriving with different packaging. The culture there is a tradition of the Minangkabau is very closely related to political communications i.e. the tradition of awarding gala sangsako used to counter service to a character with the conferring of honorary gala form sangsako. For it to be able to understand the political communication in the tradition of awarding gala sangsako in Minangkabau culture then this research aims to know the process of political communication in the tradition of awarding gala sangsako, as well as to find out the channel the political communication in the determination of recipients gala sangsako and to know public opinion formed from this tradition. This study uses qualitative methods with qualitative, descriptive approach-in the perspective of political communication.The subject consists of the Pagaruyung and the Minangkabau community leaders selected by purposive techniques. Data collection was done through interviews, documentation and obervasi. The validity test of the data using the credibility test. The data analysis techniques were reducting the data, collect data, present data, make conclusions and evaluation. From the results of the research note that (1) the process of political communication in the tradition of awarding gala sangsako are present in the process before the tradition malewakan gala sangsako, and in procession tradition malewakan gala sangsako.(2) political communication channel used in the determination of the prospective recipient of the gala sangsako was the political organization of the communication channels because the process of political communication occurs between the Minangkabau community organizations with the Pagaruyung.(3) public opinion formed is someone who gets the gala sangsakomerupakan good and Honorable people and traditions gala sangsako is a form of political communication.So it can be concluded that the tradition of awarding gala sangsako is a form of political communication in the presence of political communication that occurs in the process of awarding gala sangsako traditions in the culture of the Minangkabau.Keywords: Political communication, Gala Sangsako, Cultural of the Minangkab